2023
DOI: 10.1021/acs.energyfuels.2c02556
|View full text |Cite
|
Sign up to set email alerts
|

Energy Security and Sustainability for the European Union after/during the Ukraine Crisis: A Perspective

Abstract: The special military operation initiated by the Russian Federation (RF) against Ukraine has focused on the European Union (EU) and, to a lesser degree, U.S. fossil fuel resource dependency. The Russian Federation's economy is heavily geared toward exports of carbonbased fuels. As a result of the proximity of the EU and Ukraine, these two entities are the largest importers of RF fossil fuels. Ukraine's and EU's large population and heavy industries utilize energy in large quantities. As a result of the overreli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…The higher pore volume of MSF allowed for greater amine accommodation, consistent with ndings by other researchers. [73][74][75] As previously explained, temperature has two opposing effects on CO 2 uptakes, signicantly inuenced by the CO 2 concentration, amine loading, amine chain length, and moisture availability. Similar to humid conditions, where CO 2 uptake went through a maximum versus temperature, dry conditions had the same behavior but at a different temperature.…”
Section: Adsorption Isotherms and Selectivitymentioning
confidence: 96%
“…The higher pore volume of MSF allowed for greater amine accommodation, consistent with ndings by other researchers. [73][74][75] As previously explained, temperature has two opposing effects on CO 2 uptakes, signicantly inuenced by the CO 2 concentration, amine loading, amine chain length, and moisture availability. Similar to humid conditions, where CO 2 uptake went through a maximum versus temperature, dry conditions had the same behavior but at a different temperature.…”
Section: Adsorption Isotherms and Selectivitymentioning
confidence: 96%
“…Li et al investigated the influence of different silica nanostructure supports for PEI-functionalized adsorbents, in the form of silica nanospheres (SNPs), silica nanosheets (SNHs), and silica nanotubes (SNTs). [54] It was shown that the morphology of support plays a crucial role in CO 2 capture from flue gas, particularly the key parameters associated with ultralow emission, such as adsorption capacity, amine efficiency, thermodynamics, kinetics, cyclic stability, and temperature of optimal adsorption. SNHs enhanced the dispersion of the PEI active sites for successful mass transfer resistance reduction of CO 2 during the adsorption process.…”
Section: Polyethyleneimine (Pei)mentioning
confidence: 99%
“…The fundamental postulates of the energy sector in general, energy security, and human rights in this area, in particular, have become the subject of attention in theoretical and practical terms. The level of security and competence in the energy sector is studied (Georgiadou et al, 2023); energy security and resilience after/during crises (Liu et al, 2023); attacks on energy infrastructure aimed at democratic institutions (Lordan-Perret et al, 2019). As noted by Y. Kharazishvili et al (2021) note that systemic and strategic approaches to assessing energy security, ensuring the security of sustainable development, tools, and strategic scenarios for implementing energy security in the context of geopolitical instability are important.…”
Section: ■ Literature Reviewmentioning
confidence: 99%